Analysis of development dynamics of the program «Affordable medicines» in Ukraine and Lviv region - O. B. Blavatska; O. M. Zaliska; Ya. O. Hrynkiv; H. O. Sosnovska (The State Expert Center of the Ministry of Health of Ukraine, 2020)
Ukraine has launched a government program «Affordable Medicines» for patients with cardiovascular disease, type 2 diabetes and bronchial asthma in 2017, which reimburses essential medicines for outpatients. Since April 2019, electronic prescriptions for the «Affordable Medicines» program have been introduced. The purpose of this study was to analyze and compare the development of a government drug reimbursement program, including the dynamics of the number of prescription and dispensed electronic prescriptions for medicinal products in the «Affordable Medicines» program in 2019, both in Ukraine and at the level of Lviv city and Lviv region. For research and analysis, we have obtained statistics from the National Health Service of Ukraine (NHSU) on the number of e-prescriptions for medicines in the Affordable Medicines program and pharmacy facilities involved in the program over certain periods from April to December 2019 across Ukraine and at the level of Lviv city and Lviv region. We used informative, comparative research methods and a method of retrospective analysis of the dynamics of prescribed and dispensed e-prescriptions for medicines. The results of the study showed that Lviv region is consistently among the leaders of e-dispensing medicines. E-prescriptions are most commonly prescribed for patients aged over 65 years old with cardiovascular disease. Differences in e-appointments of pharmacies by INN at the level of Lviv city and Lviv region are revealed in comparison with the average data of Ukraine. E-prescribing has been shown to increase access to medication for patients, as at the end of 2019 through the «Affordable Medicines» program, 1.77 million patients were enrolled and 10.86 million e-prescriptions were written out, of which 9.23 million (84.94%) were released from pharmacies. Lviv region has actively implemented e-prescriptions and according to the NHSU 43% of the pharmacies in the region are connected to this system and they issue e-prescriptions, that is higher than the average data in Ukraine of 35%. The positive dynamics of the growth of e-prescriptions written and released of essential drugs from 29% to 85% indicates the effective implementation of the e-prescription in Ukraine and confirms the effective implementation of the drug reimbursement program. Considering the benefits of electronic prescriptions, reducing the number of errors, time, monitoring appointments, it is promising to expand the list of drugs, including. those that are purchased for budgetary or accounting purposes to optimize pharmaceutical assistance to the public.